The Oxford handbook of employment relations : comparative employment systems - Wilkinson, Adrian, 1963-; Wood, Geoffrey E., 1945-; Deeg, Richard, 1961- (Oxford : Oxford University Press, 2014)
This handbook is a comparative treatment of employment relations, providing frameworks and empirical evidence for understanding trends in different parts of the world.
Includes bibliographical references and index.
Description based on print version record.
Keywords: Industrial relations